Race and biovar determination of Ralstonia solanacearum in the north west of Pakistan - Muhammad Junaid; Musharaf Ahmad; Saifullah (Novel Research in Microbiology Journal)
Multiple comprehensive surveys were conducted during 2012, in order to know the current status of bacterial wilt (BW) of tomato caused by Ralstonia solanacearum (R. solanacearum), in the commercial tomato growing districts of Khyber Pakhtunkhwa (KP), Pakistan. A total of 74 locations covering all the 26 districts of the 7 divisions of KP were visited for the presence of tomato plants showing BW symptoms. According to Polymerase chain reaction (PCR), the expected 281bp band was amplified from 25 candidates of R. solanacearum isolates, thus genetically confirming them to be R. solanacearum. These R. solanacearum isolates were subjected to race identification and biovar determination tests. Race differentiation was done using hypersensitive response (HR) test on tobacco plants; whereas 10% solutions of six different sugars including disaccharides (i.e. sucrose, lactose and maltose), and sugar alcohols (i.e. manitol, sorbitol and dulcitol) in Triphenyl tetrazolium chloride (TTC) medium, were used for biovars determination. Results indicated that all PCR-confirmed R. solanacearum isolates belonged to race-1 and biovar-3. However, two isolates i.e. (R. solanacearum11-DIK1 and R. solanacearum10- MDN2) were found to belong to race-3, biovar-2.